2008
DOI: 10.1111/j.1365-2958.2008.06331.x
|View full text |Cite
|
Sign up to set email alerts
|

A previously unidentified σ factor and two accessory proteins regulate oxalate decarboxylase expression in Bacillus subtilis

Abstract: SummaryWe have investigated the function of a cell envelope stress-inducible gene, yvrI, which encodes a 22.5 kDa protein that includes a predicted s 70 region 4 domain, but lacks an apparent region 2 domain. YvrI interacts with RNA polymerase and overexpression of YvrI results in induction of OxdC, an oxalate decarboxylase maximally expressed under low-pH conditions. We have used microarray-based analyses to define the YvrI regulon. YvrI is required for the transcription of three operons (oxdC-yvrL, yvrJ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 54 publications
(75 reference statements)
2
58
0
1
Order By: Relevance
“…The B. subtilis SigO-RsoA proteins constitute an atypical two-subunit s factor (MacLellan et al, 2008(MacLellan et al, , 2009a that is activated in response to certain cell-wall-acting antibiotics and to growth under acidic conditions (Cao et al, 2002;Hachmann et al, 2009;MacLellan et al, 2009b). In this communication, we identify the protein encoded by gene rsiO as the cognate anti-s factor to SigO-RsoA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The B. subtilis SigO-RsoA proteins constitute an atypical two-subunit s factor (MacLellan et al, 2008(MacLellan et al, , 2009a that is activated in response to certain cell-wall-acting antibiotics and to growth under acidic conditions (Cao et al, 2002;Hachmann et al, 2009;MacLellan et al, 2009b). In this communication, we identify the protein encoded by gene rsiO as the cognate anti-s factor to SigO-RsoA.…”
Section: Discussionmentioning
confidence: 99%
“…1a) (MacLellan et al, 2008(MacLellan et al, , 2009a. Previous work demonstrated that deletion of the gene downstream of oxdC (rsiO, formerly yvrL) resulted in an increase in basal SigO-RsoA activity (MacLellan et al, 2008) and increased OxdC accumulation in B. subtilis cells (MacLellan et al, 2009b) suggesting that RsiO, a predicted membrane protein (Fig.…”
Section: Genetic Organization Of the Sigo -Rsoa Regulonmentioning
confidence: 99%
See 3 more Smart Citations